Cohesion and Coherence in Remarks by President Biden in the Joint Statement with Ukraine - Febrian, Muhammad Bryant Valen; Ardani, Raissa Putri; Musyahid, Rizky Agus; Maulana, Wiryawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2023)
This research paper focuses on the analysis of cohesion and coherence in the remarks made by President Biden during the Joint Statement with Ukraine. The study aims to examine the logical flow, consistency, and clarity of President Biden's statements in the context of the U.S.-Ukraine relationship. A content analysis approach is employed to analyze the speech delivered by President Biden, including key themes, messaging, and any potential inconsistencies. The findings of this analysis contribute to understanding the effectiveness of President Biden's communication strategy and the coherence of his administration's approach toward Ukraine. The analysis presents a comprehensive understanding of the cohesion and coherence exhibited by President Biden in the Joint Statement with Ukraine, offering valuable insights into the U.S. government's stance towards Ukraine and its broader foreign policy objectives. The findings of this research provide valuable insights into the effectiveness of President Biden's communication strategy and the coherence of his administration's approach toward Ukraine. By assessing the cohesion and coherence in President Biden's remarks, this analysis offers a comprehensive understanding of the administration's commitment to supporting Ukraine in various domains, including security, democracy, and economic development.